The curse of rose quay - Dean, Billie; Jolly, Sarah (Macmillan Education Australia South Yarra, Vic., 1997)
The Curse of Rose Quay by Billie Dean is a thrilling mystery novel that follows a group of friends who stumble upon an ancient legend surrounding a cursed location known as Rose Quay. As they delve deeper into the mystery, they uncover dark secrets and eerie occurrences tied to the curse, which has haunted the area for generations. The friends must work together to solve the riddle and confront the forces that seem determined to keep the curse alive. Filled with suspense and adventure, the story explores themes of friendship, bravery, and the power of belief, keeping readers on the edge of their seats as they unravel the secrets of Rose Quay.